2008
DOI: 10.1016/s1472-6483(10)60296-9
|View full text |Cite
|
Sign up to set email alerts
|

The Well-of-the-Well system: an efficient approach to improve embryo development

Abstract: Transfer of human embryos at the blastocyst stage may offer considerable benefits including an increased implantation rate and a decreased risk of multiple pregnancies; however, blastocyst culture requires an efficient and reliable in-vitro embryo culture system. In this study, the effect of the Well-of-the-Well (WOW) system consisting of microwells formed on the bottom of the culture dish was tested in three mammalian species, including humans. The WOW system resulted in significant improvement when comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 39 publications
5
54
1
Order By: Relevance
“…WOWs (semi-isolated microenvironments with 0.15-0.04 ml) on the bottom of a conventional four well dish provide a constant and suitable microenvironment for embryos and the open condition of the WOW system seems to be a good compromise between the controversial needs of large (nutrition and dilution of metabolized toxic products) and small (accumulation of autocrine and paracrine factors) volumes. Most recently, the WOW system has been used to culture human preimplantative embryos up to the blastocyst stage (Vajta et al 2008). Comparative studies on the effects of various embryo densities have generally focused on the percentage of embryos that proceed to the blastocyst or hatched blastocyst stages (Ferry et al 1994, Fujita et al 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WOWs (semi-isolated microenvironments with 0.15-0.04 ml) on the bottom of a conventional four well dish provide a constant and suitable microenvironment for embryos and the open condition of the WOW system seems to be a good compromise between the controversial needs of large (nutrition and dilution of metabolized toxic products) and small (accumulation of autocrine and paracrine factors) volumes. Most recently, the WOW system has been used to culture human preimplantative embryos up to the blastocyst stage (Vajta et al 2008). Comparative studies on the effects of various embryo densities have generally focused on the percentage of embryos that proceed to the blastocyst or hatched blastocyst stages (Ferry et al 1994, Fujita et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies examining the pattern of expression of important genes as a function of embryo culture in WOWs are still lacking. Although some pregnancies have been achieved after the transfer of human embryos derived from WOW culture (Vajta et al 2008), it is still unresolved whether the gene expression pattern of embryos culture in WOWs is affected by microenvironment and/or embryo density.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro production (IVP) of bovine embryos using single or low numbers of oocytes and embryos during culture is increasing among researchers linked to the production of embryos from oocytes collected by ovum pick-up (OPU) (see Carolan et al, 1996;Vajta et al, 2000Vajta et al, , 2008Ward et al, 2000;Goovaerts et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, studies using PDMS microfluidic channels or funnels have suggested novel solutions for oocyte manipulation, sperm sorting, and embryo culture . Microfluidic systems that mimic oviductal structures and functions for use in RT are divided into those used for sperm motility control or monitoring [50][51][52][53][54][55][56][57][58][59][60], regulation of chemical gradients for in vitro fertilization and embryo culture [61][62][63][64][65][66][67][68][69], and applying mechanical stimuli to the developing embryo [70][71][72][73][74]. Although the unique characteristics of elastomers have been exploited for microstructure fabrication and/or micro-pumping, mechanical deformation of the elastomer membrane has not been used to produce new devices for RT.…”
Section: Microfluidic Channels To Handle Sperm and Embryosmentioning
confidence: 99%
“…The well-of-the-well system (WOW) has been used successfully with embryos from a variety of species including mouse, pig, cow, and human and entails using small impressions, or microwells, of varying sizes and arrangements created in the bottom of a vessel/dish [8,61] ( Figure 6A). An alternate approach that permits a commercial means of utilizing microwells in conjunction with existing dishware in the lab involves using microwell-inserts consisting of several rows of tiny culture wells composed of PDMS [38].…”
Section: Embryo Culture Systems Using Pdms Chambers or Channelsmentioning
confidence: 99%